Changes in disability and their relationship with skin thickening, in diffuse and limited cutaneous systemic sclerosis: a retrospective cohort study. (4th May 2019) - Peytrignet, S; Manning, J; Wragg, E; Moore, T; Samaranayaka, M; Dinsdale, G; Herrick, AL
Abstract : Objective : The burden of disability associated with systemic sclerosis (SSc) is being increasingly recognized. Our aim was to test the hypothesis that changes in functional ability over time differ between patients with limited (lcSSc) and diffuse cutaneous (dcSSc) subtypes, and that in dcSSc (but not lcSSc) these changes correlate with skin thickening. Method : This was a retrospective analysis of data collected prospectively between 2005 and 2016 at a single centre. Data recorded at annual review visits included modified Rodnan skin score (mRSS) and Health Assessment Questionnaire Disability Index (HAQ-DI). Yearly rates of mRSS and HAQ-DI change were assessed by individual linear regressions, and those gradients were compared between disease groups (lcSSc/dcSSc) for each of early/late disease (less/greater than 5 years' duration). Results : The study included 402 patients (110 dcSSc, 292 lcSSc), with mean length of follow-up of 5.5 years (sd 3.5). Mean baseline HAQ-DI was 1.4 in dcSSc and 1.2 in lcSSc. In dcSSc, increased mRSS was associated with worsening disability (ρ = 0.36, p = 0.004) during early but not late disease (ρ = 0.12, p = 0.331). In lcSSc, changes in mRSS were not associated with changes in disability for early (ρ = −0.15, p = 0.173) or late disease (ρ = 0.10, p = 0.137). Conclusion : These findings confirm high disability in patients with SSc. A relationship between HAQ-DI and mRSS (worsening mRSS associated with increasing disability) was found only in patients with early dcSSc, suggesting that in other patient subgroups other factors play the major role.